Assessment of the in vitro toxicity of the disinfection byproduct 2, 6-dichloro-1, 4-benzoquinone and its transformed derivatives. (November 2019) - Hung, Stephanie; Mohan, Aarthi; Reckhow, David A.; Godri Pollitt, Krystal J.
Abstract: An emerging class of unregulated disinfection byproducts, halobenzoquinones (HBQs ), has gained recent interest following suggestions of enhanced toxicity compared to regulated disinfection byproducts. While the kinetics of HBQ hydrolysis in water have been well characterized, the stability of HBQs in cell culture media, a critical parameter when evaluating toxicity in vitro, has been overlooked. The objective of this study was: (1) to contrast the stability of a prevalent HBQ, 2, 6-dichloro-1, 4-benzoquinone (DCBQ ), in cell culture media and water, and (2) to evaluate the cytotoxicity of parent and transformed DCBQ compounds as well as the ability of these compounds to generate intracellular reactive oxygen species (ROS ) in normal human colon cells (CCD 841 CoN ) and human liver cancer cells (HepG2 ). The half-life of DCBQ in cell media was found to be less than 40 min, compared to 7.2 h in water at pH 7. DCBQ induced a concentration-dependent decrease in cell viability and increase in ROS production in both cell lines. The parent DCBQ compound was found to induce significantly greater cytotoxicity compared to transformed DCBQ products. We demonstrate that the study design used by most published studies ( i.e., extended exposure periods) has led to a potential underestimation of the cytotoxicity of HBQs by evaluating the toxicological profile primarily of transformed HBQs, rather than corresponding parent compounds. Future in vitro toxicological studies should account for HBQ stability in media to evaluate the acute cytotoxicity of parent HBQs. Highlights: The half-life of DCBQ, a prevalent HBQ, is shorter in culture media than water. Water- and media-transformed DCBQ compounds induce cytotoxicity and generate ROS. Media-transformed DCBQs induce decreased cytotoxicity vs the parent DCBQ compound. In vitro studies with extended exposures may have underestimated DCBQ cytotoxicity.